Investigation of acute effects of diclofenac sodium on rat kidney with unilateral ureteral obstruction - Yildiz, Mustafa; Pekdemir, Murat; Akpolat, Nusret; Durukan, Polat; Seckin, Dilara; Celiker, Huseyin; Rahman, Ali (Elsevier Science Bv, 2008)
Objectives: Obstruction of urine passage in anywhere from kidney to urinary bladder is named as obstructive uropathy. It is seen in renal colic patients in emergency departments. Diclofenac sodium, a non-steroidal anti-inflammatory drug, is frequently used in the treatment. This study was designed to investigate acute effects of diclofenac sodium on the kidney with unilateral ureteral obstruction. Materials and Methods: The study was performed in Experimental Investigation Centre of Firat University Faculty of Medicine. Wistar type female rats were categorized as control (I), sham (II), diclofenac (DS) (III), unilateral uretheral obstruction (UUO) (IV) and UUO+DS (V) groups. Rats were anesthesized by ketamin (5 mg/kg) and xylazine (5 mg/kg). In the IInd, IVth and Vth groups, midline abdominal incision was performed and in the IVth and Vth groups urethers were binded unilaterally. One mg of DS was given to IIIrd, IVth and Vth groups. Kidneys were sacrified in all groups. Blood and tissue samples were taken for biochemical and pathological analysis. Results: There was significant difference between the groups in pathological evaluation regarding neutrophyl, lymphocyte, and macrophage infiltration and proximal tubular dilatation (p<0.01 for all). It was found that infiltration was particularly increased in UUO group but decreased in UUO+DS group. In the biochemical analysis, there was a significant difference between the groups in respect to plasma levels of PGE(2) (p<0.01) and TXA(2) (p<0.01). When control and UUO+DS groups were compared, plasma PGE(2) (p<0.01) and TXA(2) (p<0.01) levels were found to be significanlty decreased in UUO+DS group. Conclusion: As a result, in UUO rat group in the first 5 hour, DS decreased the inflammation and tubular dilatation; but neither positive nor negative tissue level effect was determined.
Keywords: Acute unilateral uretheral obstruction; kidney; diclofenac sodium